Historical Perspective of Inborn Errors of Immunity in Turkey - Yıldız Camcıoğlu (Turkish Journal of Immunology)
This article details the development of immunology as a scientific discipline based on basic research and clinical application in Turkey. Due to the valiant efforts of the Turkish Society of Immunology (TSI), immunology has become a fundamental discipline in its own right in Turkey. Immunology Laboratories were established at İstanbul Medical School, Cerrahpaşa Medical School, and Hacettepe Medical School in 1970. Since 1974, TSI has been the driving force organizing the ''National Immunology Congress' and joint meetings with international immunology and inborn errors of immunity (IEIs) centers. The immunological education program was established in some of Turkey's most prominent medical schools during the 2000-2001 academic year. Following the establishment of the immunological programs, all facets of modern immunology and clinical medicine began to diverge. Subsequently, the Turkish National Society of Allergy and Clinical Immunology, and Clinical Immunology Society were established and initiated to organize congresses, educational meetings, courses, and webinars. With the assistance of international experts, Turkish clinical immunologists defined many gene defects in Turkish patients. As clinicians gained additional immunological experience, new techniques and practices that allowed for better diagnosis and treatment of a larger variety of different immunodeficiencies were developed. Beginning in 2011, the Ministry of Health started to regulate patient care by allowing pediatric/adult allergists and immunologists to provide patient care at the tertiary level. Screening tests for IEIs and intravenous or subcutaneous immunoglobulin replacement treatment are now being offered to all patients. Human stem cell therapy treatments are accessible for patients with T-cell deficiency, and available monoclonal therapies are provided to IEIs patients in Turkey.